2023
DOI: 10.1089/lap.2022.0546
|View full text |Cite
|
Sign up to set email alerts
|

Major Venous Repair or Reconstruction During Laparoscopic Pancreatic Surgery: A Single Center's Experience

Abstract: Background In pancreatic cancer surgery, tumor violation of blood vessels is often considered a contraindication of surgery, especially laparoscopic surgery. We had completed 17 cases of major venous repair or reconstruction during laparoscopic pancreatic surgery, and we considered that this surgical method was safe and feasible based on the skilled laparoscopic techniques.Methods Between January 2014 and March 2022. A prospective cohort of 17 patients underwent major venous repair or reconstruction. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The procedure and feasibility of LPD with major vascular resection has been described in previously published studies at our center ( 19 ). This study used 1:1 PSM to control confounding factors, such as the vascular reconstruction method and clinical baseline data, the results indicated the advantages of less intraoperative bleeding in the LPD group, with postoperative complications and long-term prognosis similar to that of the OPD group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure and feasibility of LPD with major vascular resection has been described in previously published studies at our center ( 19 ). This study used 1:1 PSM to control confounding factors, such as the vascular reconstruction method and clinical baseline data, the results indicated the advantages of less intraoperative bleeding in the LPD group, with postoperative complications and long-term prognosis similar to that of the OPD group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several institutions have reported minimally invasive surgery with major venous resection ( 19 , 23 , 24 ). Kendrick et al ( 25 ) first reported LPD combined with vascular resection and reconstruction, proved the feasibility of the technique, and proposed that with the help of a good field of view, magnification and positive intra-abdominal pressure, it might give outcomes superior to those of open surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation